Some evaluations on Lisаn Al-Din Ibn Al-Khatib as a historian in Andalucia (Eurasian Journal of Religious Studies, 2017)
An outstanding man of science and historian, Lisân Al-Din Ibn Al-Khatib (1313-1374) played an important role in the history of the medieval Muslim Spain. In his works he combined many branches of science, that is why his Muslim contemporaries called him “al-‘Allama” (“the greatest scientist”), and the Spaniards gave him an honorary title of “el Poligrafo” “the Encyclopaedist”.He owns about 60 scientific works, which occupy a special place in the history writings that make up the most complete historical annals of Muslim Spain.Ibn al-Khatib viewed history as a means of transferring information to the next generations, immortalizing the moral qualities, tracing their lineage and gaining experience.Marking his era through the official duties he had, Ibn al-Khatib has had an ongoing influence on people – with the books he wrote – especially, in the fields of history and literature, until today.